Fungal-Fungal Interactions in Leaf-Cutting Ant Agriculture - Sunshine A. Van Bael; Catalina Estrada; William T. Wcislo (Psyche: A Journal of Entomology)
Many organisms participate in symbiotic relationships with other organisms, yet studies of symbioses typically have focused on the reciprocal costs and benefits within a particular host-symbiont pair. Recent studies indicate that many ecological interactions involve alliances of symbionts acting together as mutualistic consortia against other consortia. Such interacting consortia are likely to be widespread in nature, even if the interactions often occur in a cryptic fashion. Little theory and empirical data exist concerning how these complex interactions shape ecological outcomes in nature. Here, we review recent work on fungal-fungal interactions between two consortia: (i) leaf-cutting ants and their symbiotic fungi (the latter grown as a food crop by the former) and (ii) tropical plants and their foliar endophytes (the cryptic symbiotic fungi within leaves of the former). Plant characteristics (e.g., secondary compounds or leaf physical properties of leaves) are involved in leaf-cutting ant preferences, and a synthesis of published information suggests that these plant traits could be modified by fungal presence. We discuss potential mechanisms for how fungal-fungal interactions proceed in the leaf-cutting ant agriculture and suggest themes for future research.